Impact of social support and breastfeeding success on the self-efficacy levels of adolescent mothers during the postpartum period - Veysel Can; Mehmet Bulduk; Emine Kurt Can; Nesrullah Ayşin (Reproductive Health)
Abstract Background This study aimed to explore the relationship between social support, breastfeeding success, and breastfeeding self-efficacy levels in adolescent mothers, as well as the factors affecting breastfeeding self-efficacy. Methods Following ethical approval, The Socio-Demographic Data Form, the Breast Milk and Breastfeeding Information Form, the Multidimensional Scale of Perceived Social Support (MSPSS), the Breastfeeding Self-Efficacy Short Form Scale (BFSES) and the LATCH Breastfeeding Diagnostic and Assessment Scale were used to collect data and the study was completed with 163 participants. Results The rate of exclusive breastfeeding was found to be 41.1%. Mothers who exclusively breastfed their babies had higher scores on the MSPSS, LATCH, and BFSES scales. Additionally, breastfeeding self-efficacy levels were higher among mothers who initiated breastfeeding within 1 h after birth. The study also found positive correlations between social support, breastfeeding success, and breastfeeding self-efficacy. Conclusions In conclusion, social support networks, including partners, mothers, and mothers-in-law, should be incorporated into breastfeeding training programs to help adolescent mothers leverage these resources effectively. Clinical trial number: Not applicable.